Development of the life-cycle economic and environmental assessment model for establishing the optimal implementation strategy of the rooftop photovoltaic system - Koo, Choongwan; Hong, Taehoon; Park, Joonho (Technological and Economic Development of Economy, 2018)
To maximize the life-cycle economic and environmental performance of the rooftop photovoltaic (PV) system in real projects, it is necessary to consider several factors such as regional climate factors (i.e., geographical and meteorological factors) and building characteristics (i.e., on-site installation factors, rooftop area limit, and budget limit). Towards this end, this study aimed to develop the life-cycle economic and environmental assessment model for establishing the optimal implementation strategy of the rooftop PV system. The robustness and reliability of the developed model were evaluated in terms of two perspectives: (i) for the effectiveness of the optimal solution, the optimization results were generated by considering the regional climate factors and building characteristics. Namely, the results for SIR25 (saving to investment ratio at year 25), which was set at the optimization goal, were 2.540 (Busan, southern part of South Korea), 2.485 (Daejeon, central part of South Korea), and 2.266 (Seoul, northern part of South Korea), respectively; and (ii) for the efficient computation time, the time required for determining the optimal solution was only 27 seconds. The developed model can be used to easily and accurately assess the life-cycle economic and environmental performance of the rooftop PV system in the early design phase. First published online 14 April 2016